Influence of EEG rhythms on extraversion-introversion indicators and smiles test - Lobasyuk, B. A.; Bodelan, M.; Zamkovaya, A. V. (Journal of Education, Health and Sport, 2021)
Urgency. Currently, the diagnosis of personality disorders is subjective and depends on the classifications used, the choice of the diagnostic method. The objective: to establish the probable regulatory effects of the functional state of the central nervous system according to electroencephalographic research (EEG) data in healthy individuals in providing individual psychological traits (features) of the personality, determined using Eysenck's and SMIL tests, using multivariate analysis - by methods of multiple regression and correlation analysis in extroverts and introverts, in order to diagnose the norm. Materials and methods. The psychological methods of G. Eysenck (EPI) and SMIL were carried out in electronic form and had a standard form. EEG was studied on 48 practically healthy people, students, average age 20 ± 0.5 years for 2 minutes in a state of psychosensory rest - eyes closed. The analysis of EEG files was carried out after the end of the experiments using the "Analist2" program. EEG segmentation was performed using the method of fixed intervals. The indicators of the EPI and SMIL tests were considered as the target feature (Y-s), and the indicators of the amplitudes of the EEG rhythms were considered as influencing variables (sets of X-s) and the equations of multiple linear regression were built. Results. It was shown that, in both extroverts and introverts, during periods of desynchronization, the number of statistically significant regression coefficients from the amplitudes of EEG rhythms to the indicators of Eysenck and SMIL tests was determined to be greater than during periods of synchronization. The greatest number of regression connections-relationships in extroverts under conditions of desynchronization was determined by the indicator "psychopathy", and in introverts the influence from EEG indicators along all six channels was determined by the indicators "extro-introversion" and "depression". The greatest number of regression relationships-relationships among extroverts under synchronization conditions was determined by the indicator "psychopathy", and among introverts the relationships-relationships from EEG indicators to indicators of psychological tests were evenly distributed in the amount of 2-3. Conclusions.1. In extraverts, the number of regression relationships-relations from the EEG amplitude indicators to the indicators of Eysenck's and SMIL tests was determined to be greater than in introverts. This indicates that in extraverts the formation of individual-typological personality traits to a greater extent than in introverts depends on neurophysiological mechanisms. 2. The realization of mental acts and states, verified by the indicators of the EPI and SMIL tests, is carried out mainly during periods of desynchronization. It can be assumed that periods of desynchronization, to some extent, reflect episodes of consciousness, and periods of synchronization are episodes of the unconscious. 3. The beta-2 rhythm indicator is an actual control element in the formation of individual-typological personality traits in extroverts. 4. The theta rhythm indicator is a fairly relevant control element in the formation of individual-typological personality traits in both extroverts and introverts.